The bacterium endosymbiont of Crithidia deanei undergoes coordinated division with the host cell nucleus. - Maria Cristina Machado Motta (Public Library of Science (PLoS), 2010)
In trypanosomatids, cell division involves morphological changes and requires coordinated replication and segregation of the nucleus, kinetoplast and flagellum. In endosymbiont-containing trypanosomatids, like Crithidia deanei, this process is more complex, as each daughter cell contains only a single symbiotic bacterium, indicating that the prokaryote must replicate synchronically with the host protozoan. In this study, we used light and electron microscopy combined with three-dimensional reconstruction approaches to observe the endosymbiont shape and division during C. deanei cell cycle. We found that the bacterium replicates before the basal body and kinetoplast segregations and that the nucleus is the last organelle to divide, before cytokinesis. In addition, the endosymbiont is usually found close to the host cell nucleus, presenting different shapes during the protozoan cell cycle. Considering that the endosymbiosis in trypanosomatids is a mutualistic relationship, which resembles organelle acquisition during evolution, these findings establish an excellent model for the understanding of mechanisms related with the establishment of organelles in eukaryotic cells.